2018
DOI: 10.1371/journal.pone.0203743
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood child population density as a proxy measure for exposure to respiratory infections in the first year of life: A validation study

Abstract: BackgroundAssessing exposure to infections in early childhood is of interest in many epidemiological investigations. Because exposure to infections is difficult to measure directly, epidemiological studies have used surrogate measures available from routine data such as birth order and population density. However, the association between population density and exposure to infections is unclear. We assessed whether neighbourhood child population density is associated with respiratory infections in infants.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Data on post-infancy children are limited. Previous studies on this subject ( 6 30 ) mostly included young (≤7 years) ( 6 , 11 , 12 , 14 , 18 ) or very young (≤3 years) children ( 7 , 9 , 10 , 15 17 , 19 , 22 26 , 28 ); besides, half of them were published >10 years ago ( Supplementary Table 1 ). Some of these studies (5/25) only used doctor's files or national health registries ( 7 , 15 , 20 , 21 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data on post-infancy children are limited. Previous studies on this subject ( 6 30 ) mostly included young (≤7 years) ( 6 , 11 , 12 , 14 , 18 ) or very young (≤3 years) children ( 7 , 9 , 10 , 15 17 , 19 , 22 26 , 28 ); besides, half of them were published >10 years ago ( Supplementary Table 1 ). Some of these studies (5/25) only used doctor's files or national health registries ( 7 , 15 , 20 , 21 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there was no study that evaluated the prevalence of respiratory infections and the level of population density in the area of residents. However, Lupatsch et al [39] have reported that neighbourhood child density was a poor proxy for exposure to infections in infancy.…”
Section: Discussionmentioning
confidence: 99%